Emergent Degradation Phenomena Demonstrated on Resilient, Flexible, and Scalable Integrated Photoelectrochemical Cells. Issue 48 (27th October 2020) - Kistler, Tobias A.; Zeng, Guosong; Young, James L.; Weng, Lien‐Chun; Aldridge, Chase; Wyatt, Keenan; Steiner, Myles A.; Solorzano, Oscar; Houle, Frances A.; Toma, Francesca M.; Weber, Adam Z.; Deutsch, Todd G.; et al.
Abstract: Photoelectrochemical (PEC) water splitting provides a pathway to generate sustainable clean fuels using the two most abundant resources on Earth: sunlight and water. Currently, most of the successful models of PEC cells are still fabricated on small scales near 1 cm 2, which largely limits the mass deployment of solar‐fuel production. Here, the scale‐up to 8 cm 2 of an integrated PEC (IPEC) device is demonstrated and its performance compared to a 1 cm 2 IPEC cell, using state‐of‐the‐art iridium and platinum catalysts with III–V photoabsorbers. The initial photocurrents at 1 sun are 8 and 7 mA cm −2 with degradation rates of 0.60 and 0.47 mA cm −2 day −1, during unbiased operation for the 1 and 8 cm 2 devices, respectively. Evaluating under outdoor and indoor conditions at two U.S. National Laboratories reveals similar results, evidencing the reproducibility of this design's performance. Furthermore, the emerging degradation mechanisms during scale‐up are investigated and the knowledge gained from this work will provide feedback to the broader community, since PEC device durability is a limiting factor in its potential future deployment. Abstract : Photoelectrochemical (PEC) water splitting is an attractive method to produce carbon dioxide emission‐free hydrogen fuel. However, most PEC devices are small, lacking the durability and reproducibility necessary for commercial applications. This study describes the scale‐up of an integrated PEC platform from 1 to 8 cm 2, with repeatable measurement results and good durability at two markedly different locations.